2011
DOI: 10.3109/0886022x.2010.536290
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Changes of Rat Kidney with Exposure to Chronic Thinner Inhalation

Abstract: Introduction: Organic solvents are liquid substances commonly used in everyday life at home and in industrial workplaces. These solvents are found primarily in paint as thinner. Because other narcotics are hard to find, thinner is used as a narcotic especially among youngsters of low socioeconomic level. The aim of this study is to determine the histopathological changes of rat kidney with exposure to chronic thinner inhalation. Methods: Randomized trial -the study was conducted at the animal care facility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…These changes are also similar to the results of the study 12 , who found that chronic exposure to inhalation of thinners by mice led to focal necrosis, granuloma and inflammation portal inflammation which are characteristic changes of hepatitis toxic and these changes may be due to oxidative stress It is a dangerous problem during drug development and use of many known drugs. For example, an overdose of acetaminophen (APAP) is currently the most common cause of acute liver failure in the United States and Great Britain .Drug-induced liver injury indicates that mitochondria are critical targets for drug toxicity, either directly or indirectly through the formation of reactive metabolites.…”
Section: Microscopical Apperants Changes:-supporting
confidence: 88%
“…These changes are also similar to the results of the study 12 , who found that chronic exposure to inhalation of thinners by mice led to focal necrosis, granuloma and inflammation portal inflammation which are characteristic changes of hepatitis toxic and these changes may be due to oxidative stress It is a dangerous problem during drug development and use of many known drugs. For example, an overdose of acetaminophen (APAP) is currently the most common cause of acute liver failure in the United States and Great Britain .Drug-induced liver injury indicates that mitochondria are critical targets for drug toxicity, either directly or indirectly through the formation of reactive metabolites.…”
Section: Microscopical Apperants Changes:-supporting
confidence: 88%
“…The Albino whister rats were housed in cages (metal cages) as this follows the revised EU Directive 86/609/EEC/Annex II, on Guidelines for Accommodation and Care of Laboratory Animals. They were fed with standard rodent feed and water ad libitum and maintained under well-ventilated condition [13]. The Albino more whist rat was allowed to acclimatize to the new laboratory condition for 5 days before treatment commenced.…”
Section: Animal Protocolmentioning
confidence: 99%
“…The micrographs were investigated and construed by the pathologist. The processing, sectioning, staining, microscopic examination, and interpretation were carried out as described by [13].…”
Section: Histopathology Investigationmentioning
confidence: 99%
“…An unusual suicide attempt with injection of paint thinner in the dorsum of the hand Dear Sir, Paint thinners are widely used in industry and frequently lead to chronic intoxication because of abuse. They are usually inhaled and they may have neurotoxic, myotoxic, hepatotoxic, nephrotoxic and cardiotoxic systemic effects (Argo et al, 2010;Carabez et al, 1998;Toros et al, 2011). Self-injection of the solvent inside the thorax has been reported (Solak et al, 2006), but there has been no documented case of subcutaneous administration.…”
mentioning
confidence: 99%